2018
DOI: 10.1093/mnras/sty3118
|View full text |Cite
|
Sign up to set email alerts
|

A search for warm/hot gas filaments between pairs of SDSS Luminous Red Galaxies

Abstract: We search the Planck data for a thermal Sunyaev-Zel'dovich (tSZ) signal due to gas filaments between pairs of Luminous Red Galaxies (LRG's) taken from the Sloan Digital Sky Survey Data Release 12 (SDSS/DR12). We identify ∼260,000 LRG pairs in the DR12 catalog that lie within 6-10 h −1 Mpc of each other in tangential direction and within 6 h −1 Mpc in radial direction. We stack pairs by rotating and scaling the angular positions of each LRG so they lie on a common reference frame, then we subtract a circularly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 54 publications
8
98
1
Order By: Relevance
“…As a comparison, the Planck SZ measurement of the massive cluster Abell 2319 (Ghirardini et al 2018a) is shown in the right hand panel of Figure 7. Also for comparison, the stacked Planck SZ measurement of the filamentary material between galaxies was found to be at a level of y ∼ 10 −8 (Tanimura et al 2017;de Graaff et al 2017), consistent with the pressure profile prediction at 6 × R 500 in Figure 7.…”
Section: Cluster Outskirts Via the Thermal Sunyaev-zeldovich Effectsupporting
confidence: 73%
“…As a comparison, the Planck SZ measurement of the massive cluster Abell 2319 (Ghirardini et al 2018a) is shown in the right hand panel of Figure 7. Also for comparison, the stacked Planck SZ measurement of the filamentary material between galaxies was found to be at a level of y ∼ 10 −8 (Tanimura et al 2017;de Graaff et al 2017), consistent with the pressure profile prediction at 6 × R 500 in Figure 7.…”
Section: Cluster Outskirts Via the Thermal Sunyaev-zeldovich Effectsupporting
confidence: 73%
“…For example, de Graaff et al (2019) used stacked massive galaxy pairs (mean stellar mass 10 11.3 M , virial mass ∼ 10 13 M h −1 ) to detect a filamentary thermal SZ signal. Tanimura et al (2019) similarly stacked luminous red galaxy pairs with stellar masses > 10 11.3 M , and found a filamentary thermal SZ signal larger than, but consistent with, predictions from the BAHAMAS simulations (Mc-Carthy et al 2017). Using the EAGLE simulations, Davies et al (2019) made theoretical predictions for the thermal SZ effect from the CGM at different halo masses.…”
supporting
confidence: 71%
“…In this place it should be noted that our analysis performed in this paper is free of this defect. Note also that Shafieloo et al [6] considered only the decays of the dark energy into dark components: dark matter and dark radiation, whereas we consider a general case (that is in our approach a decay of the dark energy into a visible baryonic matter is also admissible, which cannot be excluded in the light of the recently reported discovery of baryonic spindles linking galaxies [79][80][81]).…”
Section: Discussionmentioning
confidence: 99%